(untitled) (Afrika und Übersee, 2025)
This article explores lexical contact between Cushitic and Nilotic taking the proposed Cushitic language Proto Baz as point of departure. Proto Baz is a putative East Cushitic language proposed by Heine, Rottland & Vossen (1979), on the basis of words borrowed into South Nilotic. Some of the loans were already pointed out by Ehret (1970, 1971, 1974). A critical assessment of the proposed loans shows that there is more diversity in their origin than formerly thought, and that it is in fact not necessary to assume the existence of a separate language (Proto Baz) to account for the loans. Instead, the loans came from various reconstructed stages of existing Cushitic languages. We discuss different contact situations between groups of East Cushitic and South Nilotic languages, as well as the recurring challenges in historical interpretation of the available evidence. The Appendix provides the reader with an overview of the discussed lexical items from earlier sources and new proposed analyses.